MAKING OF NATIVE ANIMAL VARIETIES A NEED OF FUTURE - V. B, Kalyankar; V. B, Kalyankar; M. V, Gaikwad; P, Naik A.; N. S, Solanke; D., Shinde V. (International Journal of Psychosocial Rehabilitation, 2020)
Mother Earth has been nurturing many life forms on its biome including humans. It not just survives but also evolves them according to the native conditions available and the sun light penetration. The skin colour of native humans changing with changing latitude is the implication of the same.However greedy ness of humans for his own best service has brought together hybridisation in many life forms. The consequence of the same is depleting quality of vigour and vitality in edible things. If put ignored will kill many native plant and animal varieties available in nature.Present work illustratesneed of time is to conserve them in their own habitat and let them coevolve with us.